ANALISIS KINERJA PEGAWAI KANTOR DI PT PETRONIKA KABUPATEN GRESIK: PERFORMANCE ANALYSIS OF OFFICE EMPLOYEES IN PT PETRONIKA, GRESIK DISTRICT - Adtya Nugraha; Kharisma Rizqi F (Jurnal Teknologi dan Terapan Bisnis, 2020)
This study aims to see the performance of the office employees of PT. Petronika for 1 month. This study uses the ms excel method which filters and provides final results for the 1 month. The sample in this study is 11 employees (total sampling). 65 employee performance scores with the lowest score of performance and the highest employee performance. Factors that affect the performance of employees of PT. Petronika is an individual factor and an organizational factor. The factor that has the greatest influence on the performance of the employees of PT. Petronika for 1 month is in the middle to lower average. The results of research on the performance of the office employees of PT. PEtronika for 1 month underperformed. Improving the quality of human resources will increase the ability of employees to carry out work so that employee performance increases.